Genomic Evolution of the Long Terminal Repeat Retrotransposons in Hemiascomycetous Yeasts - Neuvéglise, Cécile; Feldmann, Horst; Bon, Elisabeth; Gaillardin, Claude; Casaregola, and Serge (Genome Research, 2002)
We identified putative long terminal repeat- (LTR) retrotransposon sequences among the 50,000 random sequence tags (RSTs) obtained by the Génolevures project from genomic libraries of 13 Hemiascomycetes species. In most cases additional sequencing enabled us to assemble the whole sequences of these retrotransposons. These approaches identified 17 distinct families, 10 of which are defined by full-length elements. We also identified five families of solo LTRs that were not associated with retrotransposons. Ty1-like retrotransposons were found in four of five species that are phylogenetically related to Saccharomyces cerevisiae (S. uvarum, S. exiguus, S. servazzii, and S. kluyveri but notZygosaccharomyces rouxii), and in two of threeKluyveromyces species (K. lactis and K. marxianus but not K. thermotolerans). Only multiply crippled elements could be identified in the K. lactis and S. servazziistrains analyzed, and only solo LTRs could be identified in S. uvarum. Ty4-like elements were only detected in S. uvarum,indicating that these elements appeared recently before speciation of the Saccharomyces sensu stricto species. Ty5-like elements were detected in S. exiguus, Pichia angusta, andDebaryomyces hansenii. A retrotransposon homologous with Tca2 from Candida albicans, an element absent from S. cerevisiae, was detected in the closely related species D. hansenii. A complete Ty3/gypsy element was present inS. exiguus, whereas only partial, often degenerate, sequences resembling this element were found in S. servazzii, Z. rouxii, S. kluyveri, C. tropicalis, and Yarrowica lipolytica. P. farinosa(syn. P. sorbitophila) is currently the only yeast species in which no LTR retrotransposons or remnants have been found. Thorough analysis of protein sequences, structural characteristics of the elements, and phylogenetic relationships deduced from these data allowed us to propose a classification for the Ty1/copiaelements of hemiascomycetous yeasts and a model of LTR-retrotransposon evolution in yeasts.